Kebijakan Keimigrasian Indonesia: Pandemi, Infrastruktur, Dan Kontrol Perbatasan - Kriswibowo, Anggadika; Napitupulu, Bong Bong Prakoso; Mushfiya, Putri; Rochman, Pekik Aulia; Mailan, Ruly (UI Scholars Hub, 2023)
The COVID-19 pandemic has posed significant challenges to immigration policies in Indonesia. The government has implemented various measures, such as a temporary ban on the entry of foreigners and tightened border control, to prevent the spread of the virus. However, the implementation of these policies faces several obstacles, including inadequate infrastructure and overlapping authorities. Therefore, this research aims to examine the post-pandemic implementation of immigration policies, focusing on the role of migration infrastructure and the effectiveness of border control. The research findings indicate that both physical and information technology infrastructure play a central role in supporting policy implementation. On the other hand, border control still faces significant challenges that need to be addressed to maintain national stability. Thus, this paper recommends increased investment in infrastructure, inter-agency coordination, and the digitization of immigration administration systems to enhance policy effectiveness in the future.